Restructuring of Global Pharmaceutical Supply Chains after COVID-19 - N. A. Volgina (Vestnik MGIMO-Universiteta)
In recent decades, global pharmaceutical value chains have been actively developing. Formed close cross-country and inter-sectoral ties contributed the Covid-19 pandemic had a significant impact on the functioning of global pharmaceutical chains. The effects of Covid-19 were overlapped previously emerging trends towards defragmentation of global pharmaceutical production. The aim of this paper is to identify possible firm strategies and models for restructuring pharmaceutical chains aimed at increasing their resilience in response to the damaging effects of Covid-19. We suppose that the resilience of the chain as a whole depends on the resilience of its separate links, and we show that the restructuring of pharmaceutical chains takes place in the form of the so-called “link” restructuring (restructuring of separate links of the chain). The paper highlights such models of “link” restructuring of sectoral cross-border chain as “zero” restructuring (stock creation); localization (including import substitution); migration (including reshoring and regionalization); globalization, which operate both in the short and long term periods. The multistage nature of global pharmaceutical chains, as well as the dynamic development of pharmaceutical outsourcing processes, have created favorable opportunities for “link” restructuring. At the same time, the features of restructuring were influenced by various factors, among which the degree of technology intensity of the pharmaceutical chain takes a key place. The paper proposes one of the possible classifications of pharmaceutical chains depending on the technologies used, where the following are distinguished: low-tech and medium-low-tech chains (production of essential pharmaceutical goods); medium-high-tech chains (production of generics); high-tech chains (production of patented drugs, production of biopharmaceuticals, production of medical equipment). The main conclusion the author comes is as follows: the higher the technology intensity of the pharmaceutical chain, the less defragmentation of pharmaceutical production will take place. Thus, in the production of high-tech biopharmaceutical goods, the most needed strategies will be regionalization and globalization of the chain links, while in the production of essential pharmaceutical goods, the strategy of localization and import substitution will be very successful (especially in the short term). This is due to the fact that as the technological effectiveness of the pharmaceutical chain increases, investment costs grow, which makes the efficiency of the chain’s functioning no less important than its resilience.